ANALISIS KETIMPANGAN PENDIDIKAN DI PROVINSI SUMATERA BARAT - Putri Anik D; Ali Anis; Muhammad Irfan (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
The purpose of this study was to analyze: (1) education imbalance, (2) the effect of education expansion on education imbalance, and (3) the correlate of education imbalance on economic growth in West Sumatera Province. This research is descriptive and asosiative, it’s describe the variable and found whether there is influence between independent variable with dependent variable. This study used Survey Sosial Ekonomi Nasional years 2005, 209 and 2013. The data examied totaled 57 observations. The analyses technique are descripyive and inductive. Inductive analyses include panel data analyses, determinant coefficient, hypothesis test and coreelation test.The result showed that: education imbalance in West Sumatera Province came to low imbalance, with the lowest imbalance on Padang City with education gini index as 0,2149. The result also showed that education imbalance on city has lower gini index than regency, (2) education expansion has a negative significantly impact on education imbalance in West Sumatera Province with regression coeffecient as 0,02557, (3) education imbalance has a negative correlation with economic growth with correlation coefficient as 0,001712.    Keywords : educatio imbalance, education expansion, economic growth